Bioethanol production from the microalgae Chlorella sorokiniana through simultaneous saccharification and fermentation using Saccharomyces cerevislae - Tatel, Nonito John (Animo Repository, 2020)
This study aimed to investigate the performance of a microalgal feedstock Chlorella sorokiniana in bioethanol production through simultaneous saccharification and fermentation (SSF). The major limiting factor of SSF is the compensation between optimum hydrolysis and fermentation parameters. There is a need to determine the effects of temperature, pH, and biomass loading on the overall ethanol yield to navigate the bioprocess more efficiently. Using a central composite design (CCD), the three parameters were optimized: temperature, pH, and biomass concentration. For each run, the enzyme mixture (cellulase and amylase) was fixed at 25 g/L, fermentation time at 72 hrs, and inoculum size of Saccharomyces cerevisiae at 20% (v/v). The freeze-dried biomass is simultaneously mixed with the enzyme mixture and the inoculum and placed inside an incubator shaker. The resulting fermentation broth was analyzed for ethanol content using GC analysis. Using Design Expert, the main effects of temperature, pH, biomass loading was determined. It was found out that the temperature increases the ethanol yield up until around 32.5ºC where it starts to decrease. Meanwhile, increasing pH or biomass loading leads to a decrease in ethanol yield. An ANOVA study was conducted, and it showed that all the variables are significant as well as the interaction effect between temperature and pH. The highest ethanol yield was calculated to be 0.507 g ethanol/g glucose at: T = 33.94 °C, pH= 5.55, and biomass concentration = 16.95 g/L. Two confirmation runs were performed with a mean ethanol yield of 0.504 g ethanol/ g glucose with an error of 0.59%. A kinetic study was conducted at the optimum parameters. Using MATLAB, the Monod kinetic parameters were determined to be μm = 0.18307 h-1, Ks = 10.067 g/L, YX/S = 0.1422, and YP/S = 0.6314. The high Ks value means a faster reaction which shows in the experiments where maximum yield can be reached within 24 hrs. The ethanol yield from C. sorokiniana using SSF is highest among other studies using microalgal feedstock. Coupled with the fast kinetics, this study has shown that Chlorella sorokiniana is a viable feedstock for bioethanol production using SSF.